The stoichiometry of TCNQ-based organic charge-transfer cocrystals - Gao, Jiaoyang (2021)
Organic charge-transfer cocrystals (CTCs) have attracted significant research attention due to their wide range of potential applications in organic optoelectronic devices, organic magnetic devices, organic energy devices, pharmaceutical industry, etc. The physical properties of organic charge transfer cocrystals can be tuned not only by changing the donor and acceptor molecules, but also by varying the stoichiometry between the donor and the acceptor. However, the importance of the stoichiometry on tuning the properties of CTCs has still been underestimated. In this review, single-crystal growth methods of organic CTCs with different stoichiometries are first introduced, and their physical properties, including the degree of charge transfer, electrical conductivity, and field-effect mobility, are then discussed. Finally, a perspective of this research direction is provided to give the readers a general understanding of the concept.